تقريب الدوال العقدية على أسرة جزئية من منحنيات كارلسون - علي محمد; سويقات محمد; كنج أحمد (Latakia University Journal -Basic Sciences Series, 2014)
درسنا في هذا البحث مسألة تقريب الدوال العقدية من فضاء أورليتش على أسرة جزئية من أسرة منحنيات كارلسون تدعى منحنيات ديني الملساء إلى دوال كسرية بواسطة كثيرات حدود تتعلق بمجاميع دزياديك الناتجة عن كثيرات حدود فابير, معتمدين في الوصول إلى الهدف المنشود على بعض مفاهيم التحليل العقدي مثل صيغ سوخوتسكي. We study in this research approximation of complex functions from Orlicz space on a subclass of Carlson curves, which called Dini smooth curves to rational functions by using polynomials related with Dzjadyk sums which obtained from Faber polynomials. We depend on some concepts of complex analysis such as formulas of Sokhotski to reach the desired goal.